Bombay Anna : The Real Story and Remarkable Adventures of the King and I Governess - Morgan, Susan, 1943- (Book collections on Project MUSE., 2008)
If you thought you knew the story of Anna in The King and I, think again. As this riveting biography shows, the real life of Anna Leonowens was far more fascinating than the beloved story of the Victorian governess who went to work for the King of Siam. To write this definitive account, Susan Morgan traveled around the globe and discovered new information that has eluded researchers for years. Anna was born a poor, mixed-race army brat in India, and what followed is an extraordinary nineteenth-century story of savvy self-invention, wild adventure, and far-reaching influence. At a time when mos.